Baroreflex sensitivity and heart rate variability in conscious rats with myocardial infarction - Krüger, Carsten; Kalenka, Armin; Haunstetter, Armin; Schweizer, Mark; Maier, Christoph; Rühle, Ulrike; Ehmke, Heimo; Kübler, Wolfgang; Haass, Markus (American journal of physiology. Heart and circulatory physiology, 1997)
The baroreflex sensitivity (BRS) and the heart rate variability (HRV) were studied in conscious rats after myocardial infarction (MI; induced by coronary artery ligation) and after sham operation (SH). BRS was determined by linear regression of R-R interval vs. arterial pressure changes induced by nitroprusside or methoxamine (intravenous bolus). HRV was calculated from 3-min electrocardiogram recordings. Left ventricular end-diastolic pressure and plasma atrial natriuretic peptide were increased after MI; plasma norepinephrine and basal heart rate (HR) remained unchanged. At 3 and 28 days after MI, BRS was reduced as indicated by decreased reflex bradycardia (RB) (MI, 0.66 ± 0.13 and 0.78 ± 0.07 ms/mmHg; SH, 1.27 ± 0.16 and 1.48 ± 0.14 ms/mmHg, respectively;P < 0.05 MI vs. SH). At 56 days after MI, BRS was normalized. RB was unaffected by atropine 3 and 28 days after MI but reduced in all other groups. The increase of basal HR by atropine 3 and 28 days after MI was less than in all other groups. HRV (SD of mean N-N interval, coefficient of variance, low- and high-frequency power; studied at 28 and 56 days) was similar in all groups. It is concluded that BRS is transiently depressed in rats with left ventricular dysfunction after MI probably due to a reduced reflex vagal activity. Even though basal HR and HRV are unchanged after MI, a temporary attenuation of tonic vagal activity is unmasked after autonomic blockade.
Gesehen am 03.12.2024